COSMOPOLITAN ITALY IN THE AGE OF NATIONS transnational visions from the. - Tortarolo, Edoardo, 1956- ([S.l.] : ROUTLEDGE, 2022)
Modern Italian historiography has undergone a substantial revision in the last quarter of a century. From an almost exclusive focus on the process of nation-building, the attention of historians has shifted. The most innovative research is now devoted to assessing to what extent the cosmopolitan attitude that was evident in the late eighteenth century morphed, but did not disappear, in the ensuing two centuries. The essays in this volume make the case that the age of nations had a profound impact on Italian history and contributed to the creation of an Italian identity within the framework of well-functioning imperial and global networks. They also acknowledge that the process of national individualization carried with it a variety of aspects that reconnected Italian history to the foreign cultures that were undergoing constant self-fashioning. Cosmopolitan Italy in the Age of Nations: Transnational Visions from the Eighteenth to the Twentieth Centurywill be of interest to scholars throughout the world and intellectual and transnational historians.
Keywords: Italy -- History -- 1849-1870.; Italy -- History -- 1849-1870 -- Historiography; Italy -- Civilization; National characteristics, Italian; Cosmopolitanism -- Italy -- History; HISTORY / Europe / Italy; HISTORY / Historiography; HISTORY / Modern / General